KONSEP UKHUWWAH ISLAMIYYAH SEBAGAI MATERI PAI - Ayoeb Amin (Universitas Islam Sultan Agung, 2018)
Violent, brutal, and horizontal conflicts, as well as verbal abuse and slander on social media that sparked hatred in this country raise questions. Why did the Indonesian people who had been known friendly suddenly become violent? Is hospitality a forced attitude? Is the glue of unity called nationality not strong enough? Or are there other factors that trigger the emergence of violence and conflict? This paper will discuss about the concept of the Ukhuwwah Islamiyyah which is expected to become an Islamic Education material in schools and madrasah-madrasah throughout Indonesia. By understanding the meaning of Ukhuwwah, it is hoped that the Indonesian people will be more mature in living in a society, nation, and state. This article using a religious approach, because the majority of the population of Indonesia is Muslim. It is hoped that through this approach it can achieve the desired goals, not even be disastrous. Violent, brutal, and horizontal conflicts, as well as verbal abuse and slander on social media that sparked hatred in this country raise questions. Why did the Indonesian people who had been known friendly suddenly become violent? Is hospitality a forced attitude? Is the glue of unity called nationality not strong enough? Or are there other factors that trigger the emergence of violence and conflict? This paper will discuss about the concept of the Ukhuwwah Islamiyyah which is expected to become an Islamic Education material in schools and madrasah-madrasah throughout Indonesia. By understanding the meaning of Ukhuwwah, it is hoped that the Indonesian people will be more mature in living in a society, nation, and state. This article using a religious approach, because the majority of the population of Indonesia is Muslim. It is hoped that through this approach it can achieve the desired goals, not even be disastrous.